Purification and Characterization of Plantaricin LPL-1, a Novel Class IIa Bacteriocin Produced by Lactobacillus plantarum LPL-1 Isolated From Fermented Fish - Wang, Yao; Qin, Yuxuan; Xie, Qing; Zhang, Ying; Hu, Jinrong; Li, Pinglan (Frontiers in Microbiology, 2018)
Bacteriocins are ribosomally synthesized peptides or proteins possessing antibacterial activity against foodborne pathogens and spoilage bacteria. A novel bacteriocin, plantaricin LPL-1 was determined as a class IIa bacteriocin according to the YGNGV motif, and producer strain Lactobacillus plantarum LPL-1 was identified based on physio-biochemical characteristics and 16S rDNA sequence. The novel bacteriocin, plantaricin LPL-1 was purified by salt precipitation, cation exchange, gel filtration and reverse-phase high-performance liquid chromatography (RP-HPLC). The molecular mass of plantaricin LPL-1 was 4347.8467 Da by Matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF-MS) analysis and entire amino acid sequence of plantaricin LPL-1 was VIADKYYGNGVSCGKHTCTVDWGEAFSCSVSHLANFGHGKC. Plantaricin LPL-1 possessed the merits of easy degradation by proteases, wide pH stability (2-10), high thermal stability (121 ℃, 20min), surfactants stability and bactericidal activity against foodborne spoilage and pathogens bacteria. The mode action and membrane permeabilization of plantaricin was identified. The information of plantaricin LPL-1 indicated that it is not only a novel class IIa bacteriocin, but also a promising natural and safe biologic preservative for the food preservation industry.